Ontogenetic mechanisms of contractive apparatus development in cardiomyocytes. - Marchenko, D. G.; Tverdokhlib, I. V. (Морфологія / Morphologia / Morfologìâ, 2012)
The review is devoted to the analysis of structural and functional features of the contractive apparatus development of myocardium in the prenatal and postnatal ontogenesis. Miofibrillogenesis mechanisms in different heart chambers and areas of the cardiac wall are primarily similar, but information on their degree of gravity, balance and speed of the various myocardial sections are controversial. Thanks to analysis of numerous morphological and stereometric features may be able to find the most complete amount of information about the formation of certain structures of the contractive apparatus. The process of its formation in experimental animals and humans begin early in prenatal ontogenesis, however, many of the issues underlying this process, remain unsolved, which necessitates the use and combination of different research methods. Analysis of the issues concerning the formation of the miofibrillar apparatus components in both normal and under the influence of endogenous and exogenous factors remains significant today.